Sosialisasi Pengelolaan Sampah Rumah Tangga Menjadi Eco-Enzyme - -, Dyah Sari Ningsih (STAI Terpadu Yogyakarta, 2024)
Household waste management is becoming increasingly important in the context of environmental sustainability. Awareness of the importance of waste management has not been optimal, especially in producing eco-enzymes as an environmentally friendly solution. This research aims to increase community participation in the management of household waste into eco-enzymes, as well as identify the main obstacles and measure the success of the implementation of the program. Methods used include participatory surveys to collect initial data, interactive training to improve knowledge and skills, and periodic evaluations to monitor progress and evaluate program effectiveness. The implementation of the program has succeeded in increasing public awareness about the importance of managing household waste into eco-enzymes. Key barriers such as lack of knowledge and access to technology are successfully overcome through a participatory approach. The evaluation showed a significant increase in the number of eco-enzymes produced, showing success in changing community behavior related to waste management.